THE RELATIONSHIP BETWEEN EMPATHY AND FRIENDSHIP QUALITY IN YOUNG ADULTS - Mondal, Pritha; Santosh, Shivani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Objectives: Despite the fact that social media has numerous negative side effects, it cannot be denied that it has helped in making the nexus of individuals stronger. We live in a networked society where relationships are power. It is high time to find out whether Empathy, a basic human trait can influence the quality of friendships that one forms online. Methods: 197 emerging adults have been selected by means of purposive sampling from emerging adults in and around the city of Kolkata, West Bengal, India by keeping in mind certain criteria. They were given self report inventories of Perth Empathy Questionnaire (PES) and Friendship Quality on Social Network Sites Questionnaire (FQSNSQ) and data was collected accordingly. Results: There is a positive and significant relationship between the two variables – empathy and friendship quality at 0.01 levels. Empathy explained approximately 23% of the variance of the Friendship Quality. for each point increase in Empathy, the predicted Friendship Quality will increase by approximately 2.4 points. Conclusion: There is a moderate and positive relationship between empathy and friendship quality meaning that friendship quality improves with the increase in empathy within the individual.